Assertive Speech Acts in the Second Debate Event for Vice Presidential Candidates of the Republic of Indonesia 2024 - Pitriyasari; Alber (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research aims to describe and analyze assertive speech acts in the debate event for the second candidate for Vice President of the Republic of Indonesia 2024. The method used in this research is a content analysis method with a qualitative approach. The qualitative approach is an approach that examines scientific objects in the form of narrative texts, while the content analysis method is a method that involves an in-depth discussion of the content of written information. The data source for this research is the KPU RI YouTube channel which is currently hotly discussed and watched by the wider community. The data collection techniques used in this research are observation techniques, note techniques, and documentation techniques. In this research the author found 43 assertive speech acts, consisting of 26 speech acts of informing, 6 speech acts of suggesting, 5 speech acts of stating, 1 speech act of reporting, 3 speech acts of complaining, 1 speech act of demanding and 1 speech act of disappointing. Based on the utterances spoken, the speech act with the most is the speech act of telling as many as 26 utterances because this speech act contains information that one wants to give to the interlocutor and the general public, while the utterances with the fewest are the speech act of reporting, the speech act of demanding and the speech act of jealousy each with 1 statement. So, it can be said that an assertive speech act is a speech act that binds the speaker to the truth of what is being said, therefore the speaker should pay attention to his speech when speaking, especially to the general public